Garlic Extract (Allium sativum L.) Effectively Inhibits Staphylococcus aureus and Escherichia coli by Invitro Test - Agnina Listya Anggraini; Ratih Dewi Dwiyanti; Anny Thuraidah (Tropical Health and Medical Research, 2020)
Infection is a disease caused by the presence of pathogenic microbes, including Staphylococcus aureus and Escherichia coli. Garlic (Allium sativum L.) has chemical contents such as allicin, alkaloids, flavonoids, saponins, tannins, and steroids, which can function as an antibacterial against Staphylococcus aureus and Escherichia coli. This study aims to determine the antibacterial properties of garlic extract powder against Staphylococcus aureus and Escherichia coli. This research is the initial stage of the development of herbal medicines to treat Staphylococcus aureus and Escherichia coli infections. The antibacterial activity test was carried out by the liquid dilution method. The concentrations used were 30 mg/mL, 40 mg/mL, 50 mg/mL, 60 mg/mL and 70 mg/mL. The results showed that the Minimum Inhibitory Concentration (MIC) against Staphylococcus aureus and Escherichia coli was 40 mg/mL and 50 mg / mL. Minimum Bactericidal Concentration (MBC) results for Staphylococcus aureus and Escherichia coli are 50 mg/mL and 70 mg/mL. Based on the Simple Linear Regression test, the R2 value of Staphylococcus aureus and Escherichia coli is 0.545 and 0.785, so it can be concluded that there is an effect of garlic extract powder on the growth of Staphylococcus aureus and Escherichia coli by 54.5% and 78.5%. Garlic (Allium sativum L.) extract powder has potential as herbal medicine against bacterial infections but requires further research to determine its effect in vivo.